1996
DOI: 10.2307/3432695
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Reactions to Organic Dust Exposures: Development of an Animal Model

Abstract: Acute inhalation of organic dusts such as cotton, hay, silage, grain, animal confinement, or compost dust can result in illness characterized by fever, pulmonary inflammation, chest tightness, and airway obstruction. These agricultural materials are complex mixtures of plant, bacterial, and fungal products. Elucidation of the time course of disease onset, the mechanisms of disease progression, and the identity of etiologic agents is essential for effective prevention and treatment. Toward this end, animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
1
0
3
Order By: Relevance
“…The inhalation exposure system used in these studies was previously adapted from the Pitt 3 generator and utilized by NIOSH to allow nose-only exposure of mice to fungal conidia [24,32,33]. Clumps of A. versicolor-covered rice grains were broken apart by hand in an antistatic bag (LJY, Brighton, CO, USA) and placed in an acoustical particle generator.…”
Section: Conidia Aerosolizationmentioning
confidence: 99%
“…The inhalation exposure system used in these studies was previously adapted from the Pitt 3 generator and utilized by NIOSH to allow nose-only exposure of mice to fungal conidia [24,32,33]. Clumps of A. versicolor-covered rice grains were broken apart by hand in an antistatic bag (LJY, Brighton, CO, USA) and placed in an acoustical particle generator.…”
Section: Conidia Aerosolizationmentioning
confidence: 99%
“…[1][2][3] Sebelumnya ODTS dikenal sebagai atypical famer's lung, silo unloader's syndrome dan inhalation fever (mill fever, humidifier fever atau grain fever). [4][5][6][7][8] Gejala yang terjadi pada ODTS biasanya berupa demam yang timbul setelah terinhalasi debu organik. Gejala yang timbul tergantung dari tempat kerjanya.…”
Section: Pendahuluanunclassified
“…Bahkan kepustakaan lain menyebutkan dapat sembuh dalam waktu 24 jam. [6][7][8][9][10][11][12][13][14]…”
Section: Definisiunclassified
See 1 more Smart Citation
“…LPS is ubiquitous in the environment and especially abundant in the air on farms, in cotton textile factories, and in many other sites that are rich in organic dusts. Many studies have reported adverse effects in both humans and animals associated with inhalation exposure to organic dust. These studies have concluded that organic dust generated by human activities is sufficient to cause certain health issues. Endotoxin concentrations of 1000–2000 ng/m 3 [approximately 10000–20000 endotoxin units (EU)/m 3 ] may produce organic dust toxic syndrome (ODTS) and at concentrations of 100–200 ng/m 3 (approximately 1000–2000 EU/m 3 ) may induce bronchoconstriction. , Levels above 100 EU/m 3 significantly increased the risk of chronic bronchitis ( p < 0.0001) .…”
Section: Introductionmentioning
confidence: 99%